UI/UX Redesign of SMK Negeri 4 Samarinda Website Using UCD Approach: UI/UX Redesign of SMK Negeri 4 Samarinda Website Using UCD Approach - Renaldy; Farindika Metandi; Tommy Bustomi (JURNAL PENGELOLAAN LABORATORIUM SAINS DAN TEKNOLOGI, 2025)
The website of SMK Negeri 4 Samarinda serves an important function in communication and information dissemination, but has several shortcomings, such as unattractive interface design, outdated information, and limited interaction features. This research aims to redesign the user interface (UI) and user experience (UX) using the User Centered Design (UCD) approach. The research method includes four stages: understanding the user context, determining user needs, designing solutions, and evaluating against needs. Data was collected through focus group discussion (FGD) and usability testing using System Usability Scale (SUS) and Maze Design. The results showed that the new design prototype improved the SUS score from 61.87 (“Marginal Low” category) to 77.43 (“Acceptable” category). This improvement was also seen in the aspects of aesthetics, layout, and ease of navigation. The conclusion of this study confirms that the UCD method is effective in improving the quality of website UI/UX, there by increasing user satisfaction.